A Spatial Point Process for Estimating the Probability of Occurrence of a Traffic Accident - Anastassios Karaganis; Angelos Mimis (European Regional Science Association (ERSA), 2006)
In this paper a pioneer method for evaluating the probability of occurrence of a traffic accident in different segments of national road is described. The line segments describing the road have been divided into sections and for each one of those sections it is assumed that the probability of a traffic accident follows an inhomogeneous Poisson distribution. The overall model is build up by using a spatial point process. The Poisson parameter is estimated with the help of a spatial SUR method which exploits the characteristics of national road as described by a specially designed weight matrix. This methodology has been applied to data collected from the Greek national road and has been analyzed in this perspective. Specifically the influence of weather conditions as well as the presence of daylight has been examined.
Keywords: 330